Implementing Aspects Of Integrity In Student Environment As a Corruption Prevention Effort - Muhammad Guntur Nugroho; Meli Amalia; Selvi Komalasari; Dea Amelia; Nurani Saidah Latifah; Masduki Asbari (Journal of Community Service and Engagement, 2022)
This article aims to understand the dangers of corruption for the State and society and is intended to guide young students to avoid committing acts of corruption. Many political figures who commit acts of corruption because of this, even educated people cannot be separated from corruption, we can draw that high education is not enough to avoid corruption because that is why a strong mentality is needed to maintain honesty, responsibility, and trust that has been given. given to work. Honesty itself must be improved because there are many examples of corruption that occur around us, but we do not realize it because of this we must understand broadly the meaning of corruption itself.